Behavior Analysis of Return Intention Revisit: The Role of Destination Service Quality Through End Statisfaction in Bali Yellow Waterfall Tourism - Meryawan, I Wayan; Wijaya Kesuma Suryawan, Tjokorda Gde Agung; Handayani, Made Mulia; Eka Idayanti, I Dewa Agung Ayu; Fitriandari, Mahayanti (Universitas Negeri Yogyakarta, 2025)
The degradation of tourist satisfaction behavior and low service standards has lowered the awareness of the behavioral intention of tourists to revisit certain tourist attractions. This is a benchmark for tourism object service providers to increase the behavioral intention of tourists to visit again, especially in waterfall tourism. This study analyzes the role of visitor satisfaction as an impact on the service quality and the behavioral intentions of tourists who have returned to Bali's Yellow Waterfall tourism. Adopting a quantitative research design, the selection of respondents was referred to as purposive random sampling based on criteria, with 100 respondents. The analytical method involving SEM-PLS 4, including direct and indirect hypothesis tests, the study revealed that the level of visitor satisfaction is a significant predictor as a mediator of the relationship between destination service quality and return visit intention. Furthermore, research shows that the quality of service felt by visitors does not have a significant direct influence on the intention of tourists to revisit. This finding recommends that waterfall tourism service providers improve service quality standards and meet visitor expectations to strengthen the sustainability of the intention to revisit.